2021
DOI: 10.1111/jonm.13259
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional factors affecting care needs in daily living among community‐dwelling older adults: A structural equation modelling approach

Abstract: Aims To develop a model illustrating the factors that can influence care needs in daily living (CNDL) of older adults and the pathways between these. Background The care needs in community‐dwelling older adults have increased sharply. A better understanding of the elderly's CNDL would thus help policymakers define which types of support and services should be given. Methods A multicentre study with structural equation modelling was conducted in this study. We recruited 3,448 community‐dwelling older adults in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…This may indicate that the experience of being assisted among the home‐based elderly is affected by their characteristics and level of perception. Thus, it may be necessary to direct more volunteers to understand deeply the actual needs of the elderly to provide practical assistance 13 . Furthermore, negative experiences associated with receiving volunteer services may affect their willingness to ask for help.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may indicate that the experience of being assisted among the home‐based elderly is affected by their characteristics and level of perception. Thus, it may be necessary to direct more volunteers to understand deeply the actual needs of the elderly to provide practical assistance 13 . Furthermore, negative experiences associated with receiving volunteer services may affect their willingness to ask for help.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in some cases the present care institutions and home‐based care service centres fail to meet the diversified needs of the elderly, such as spiritual comfort and health guidance 10,11 . Furthermore, some older adults are unwilling or unable to seek professional care services due to economic constraints 12,13 . It has been reported that about 55% of the elderly in China do not have their care needs met 14 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the proportion of needs, the top six items of community nursing needs were regular health assessment, self-health monitoring guidance, general disease care, nutrition and diet, community emergency rescue, and dynamic management of filing information, which was similar to the research results of Jin L [6] and others. The nursing needs in the top six places were all more than 60%, which showed that people's health awareness is enhanced and more and more people pay attention to their own health problems [7]. Therefore, community health service centers should focus on health promo-tion projects, enhance the self-care and safety awareness of the elderly, and promote their physical and mental health; At the same time, institutions should carry out project services according to the needs of the elderly, especially health assessment, self-health monitoring guidance and general disease care, are carried out, so that every elderly person in the jurisdiction can truly feel the community health service.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies have only analyzed the elderly's willingness to use community home-based care services [13][14][15], and few surveys have shown the obstacles and in uencing factors (e.g. physiological and social disadvantages, age, economic level, family support, health status, and other related effects) of seniors in the community-initiated calls for help [16,17].…”
Section: Introductionmentioning
confidence: 99%